ATP synthase inhibition, an overlooked confounding factor in the mitochondrial stress test - Jesse Corbin; Eric A. Lehoux; Isabelle Catelas (PLoS ONE, 2025)
The mitochondrial stress test, a widely used procedure to study energy metabolism using extracellular flux analysis, involves the inhibition of ATP synthase (a.k.a. complex V [CV]). This inhibition was recently shown to cause a glycolysis-dependent underestimation of two key mitochondrial respiration parameters, maximal respiration (MR) and spare respiratory capacity (SRC), in tumor cells. However, it is unknown if test substances (toxins, drugs, signaling molecules, etc.), especially those affecting glycolysis, can impact the underestimation of MR and SRC caused by CV inhibition and thereby produce potentially erroneous results. The objective of the present study was to determine if the inhibition of CV in the mitochondrial stress test can act as a confounding factor when measuring MR and SRC in intact non-tumor cells exposed to exemplificatory test substances that affect energy metabolism: Ni2+ and lipopolysaccharides (LPS). Murine bone marrow-derived macrophages were exposed to Ni2+ (0–72 ppm) or LPS (0 or 1 µg/mL), and oxygen consumption rates were measured by extracellular flux analysis using the mitochondrial stress test, with and without CV inhibition. Results showed that CV inhibition masked the decrease in MR induced by Ni2+ or LPS. It also caused the lack of a statistically significant effect of Ni2+ on SRC to present as an increase of SRC, and the LPS-induced decrease of SRC to be masked. Results further showed that these erroneous results arose because exposure to Ni2+ or LPS reduced the underestimation of MR and SRC caused by CV inhibition. This phenomenon was associated with increased glycolytic flux. Finally, results confirmed that underestimation of MR and SRC induced by CV inhibition can occur in non-tumor cells. In conclusion, the present study demonstrates that CV inhibition can act as a confounding factor leading to erroneous conclusions when the mitochondrial stress test is used with intact cells exposed to test substances.